Fostering leadership skills of technology professionals in startups - Lydia Fioravanti, Maria; H. S. de Morais, Paulo; Francine Barbosa, Ellen (RENOTE, 2021)
This paper presents an investigation on how the startup environment fosters the development and improvement of the leadership skills of technology professionals. From the beginning of the 90s, new products and new technologies began to appear at a much faster pace and, since then, significant changes have occurred in corporate, academic environ-ments and in everyday interpersonal relationships. In this scenario, new types of business have also emerged, such as startups, considered an innovative enterprise, with the poten-tial to grow and scale. Minds ahead of all this innovation were necessary and, therefore, a new type of leader emerged. A leader who not only guides the followers but encourages leadership by them. Particularly in the startup environment, leadership becomes even more fundamental. As these entrepreneurs must keep these organizations in constant and strong growth, the ability to manage and motivate people to follow the same path becomes an essential part of the process. In this context, we aimed to answer the following research question: “How do the startup environments foster the development and improvement of the leadership skills of technology professionals?”. Aiming to answer the posed research question, we conducted a case study with four subjects. In this paper, we discuss each step of the case study and present the gathered results. As a result, we have identified three main categories of factors that promote the development and improvement of such professionals: open culture, leadership skills, and accelerated growth.